Implementation of Governance in the Treated Water Industry using the Enterprise Architecture Framework - Amanda, Djaja; Makmur, Amelia; Santoso, Handri (Politeknik Ganesha Medan, 2023)
Today, the development of information technology is very sophisticated in supporting the company's operations. It is undeniable that all companies take advantage of this technology, starting from service to customers to the company's internal operations. Water utility companies basically process raw water into clean water that is ready to be used for household purposes, industrial purposes, offices, and many other uses. Therefore, the processing industry is very much needed by the community. Moreover, it is state tax revenue in the non-oil and gas sector. Therefore, information technology is very necessary for controlling and operating at this water treatment company. Before implementing an information system or an ongoing information system, a guide is needed for implementing the system. All aspects of information technology that support the company's business serve as input in building an integrated system. Business process trimming is needed in order to build better performance. In terms of implementing enterprise architecture, the chosen framework is The Open Group Architecture Framework (TOGAF). while the method chosen is the Architecture Development Method (ADM). The purpose of this research is to apply an enterprise architecture to a water treatment company to produce a blueprint and an IT roadmap within five years to provide the best service for customers. The focus of the discussion on Governance Implementation in this company's system uses Waterfall-based Project Management. By combining the TOGAF ADM Framework in the domains of Architecture Change Management, Implementation Governance, and Migration Planning with the Project Management Body of Knowledge Method, it produces new methods that complement each other.